CARICOMP seagrass biomass from 1992 to 2012 at 51 sites within the Wider Caribbean [dataset] - van Tussenbroek, Brigitta I. (2026)
This dataset encompasses seagrass biomass from a long-term Caribbean-wide seagrass monitoring initiative: the Caribbean Coastal Marine Productivity (CARICOMP) program. Seagrass monitoring was conducted at 22 sites with 51 sampling stations from 1992 until 2012, although many concluded the monitoring program before 2007. There were one to six sampling stations per site. Monitoring included seagrass sampling using corers (diameters ranged from 10.7 cm to 20.0 cm) in four to six replicates at each station and sample processing. Sampling frequencies and periods varied among sites. The dataset includes a total of 1917 entries of Thalassia testudinum and "OtherSeagrass" (in most instances Syringodium filiforme) above and below ground biomass (gDW/m2). The dataset also includes calcareous and fleshy algae biomass (gDW/m2). Unintentional errors from potential variability in decalcification success using a weak acid (HCl 10%) should be taken into consideration in regards to calcareous algae biomass. Sampling replication, frequency, and dates varied among sites.